Combined solar heating and air-source heat pump system with energy storage: thermal performance analysis and optimization. (2017) - Yin, Zhang; Enshen, Long; Xinhui, Zhao; Zhenghao, Jin; Qinjian, Liu; Fei, Liang; Yang, Ming
Abstract: As renewable and clean energy source, solar energy has been widely used for building energy supply. However, due to its instability, solar heating system often works with auxiliary heat source and thermal energy storage (TES) equipment, in order to maintain steady hot water supply for space heating. In this paper, the analytical model is established for a hybrid heating system, containing solar collector, air-source heat pump and water tank. Moreover, its thermal performance and relationship with climatic parameters are investigated. Aimed at maximizing the overall energy conversion efficiency of such a hybrid heating system, the optimal operation strategy and heating load ratio of each subsystem are determined through inverse problem method. The results show that overall energy efficiency decreases with declining solar radiation and outdoor air temperature. The optimal operation strategy is as follows: during the daytime, solar collector is activated at full capacity as long as solar radiation is high enough and the extra hot water is stored in the tank; in the night, the water tank release heat initially; air-source heat pump works to make up for the insufficient part throughout the whole day. The case study indicates that heat pump, TES equipment and solar direct heating account for 66.5%, 23.1% and 10.4% of total heating load respectively in a typical winter day. Under such situation, the electricity consumption of the whole system can be reduced by 33% compared to traditional heating system (i.e., single heat pump). This work can provide guidance for practical design of heating system with multiple heat source and TES equipment.